Resistant Uropathogens in Gulmi Hospital: High Time to Take Action - Shrestha, Reena; Pachya, Uttam; Thapa, Tulsi R; Thapa Pachya, Ambika (Journal of Institute of Medicine Nepal, 2022)
Introduction: Recent study in Nepal showed 29.5% culture positive cases of Urinary Tract Infections (UTIs). Extensive consumption of broad-spectrum antibiotics leading to increased AMR rates amongst uropathogens. This study has been carried out to determine the proportion and types of uropathogens causing infections and their antibiotics susceptibility pattern based on WHO classification of antibiotics- access, watch and reserve ('AWaRe') categories. Methods: Record review of the urine isolates with antibiotic susceptibility testing reported from Laboratory of Gulmi Hospital from April 2019 to April 2021. Ethics approval was obtained from Nepal Health Research Council (NHRC). Calculation of frequencies and proportions and cross-tabulation was done. Results: Bacterial yield was found in more than one-third of the total 315 samples. Majorities (84.48%) of them were gram negative bacteria. More than three-fourth of the urine isolates were of female. Urinary isolates showed variable resistance to the 'access' and 'watch' group of antibiotics. There was high resistance to the conveniently prescribed antibiotics like cefixime, ciprofloxacin, ofloxacin, for UTIs. Among tested urine isolates, 75.7% were sensitive to Nitrofurantoin. Conclusion: The yield of urine culture was 36.83% in our study with higher proportions in female. The resistance was high for conveniently prescribed antibiotics. Sensitive antibiotics like Nitrofurantoin were incorporated in the empirical therapy for UTI in this hospital after the study. It is an awakening call to implement measures to strengthen antimicrobial surveillance with inclusion of the peripheral hospitals to the reporting by capacitating them for quality reporting of the antibiograms.